Business Partnering in Risk Management: A Resilience Perspective on Management Accountants' Responses to a Role Change* - Tillema, Sandra; Trapp, Rouven; van Veen‐Dirks, Paula (Contemporary Accounting Research, 2022)
ABSTRACT This study uses a resilience perspective to examine the opportunities and challenges that management accountants may experience when they are given a role as a business partner in risk management. Drawing on insights from an in‐depth case study in a large European bank, our study sheds light on management accountants' responses to a change from a compliance‐oriented role to a business partner role. In the bank studied, part of the management accountants' new role was to balance various performance objectives and thereby to incorporate risk considerations in managerial decision‐making. Our findings suggest that this role challenged the management accountants due to the ambiguity inherent in the role and also due to unfavorable conditions that surrounded the role change. We find that these circumstances culminated in a move backward, with the management accountants falling back on practices that were consistent with the values and beliefs they had developed in their previous role. In doing so, they emphasized what the resilience literature labels “well‐learned responses.” These responses contributed to an emphasis on a narrow risk management approach and had implications for the management accountants' long‐term position within the organization. We discuss these findings against the background of previous research that suggests that management accountants move forward to the business partner role by engaging in job crafting (i.e., adapting their work) or identity work (i.e., redefining their role identity). By utilizing the concepts of lingering identities and identity asymmetries to explain the management accountants' move backward, we also shed light on new facets related to role identity.